Prevalence of mental disorders among young people living with HIV: a systematic review and meta-analysis - Zhan, Shenao; Ouyang, Fei; Zhai, Wenjing; Yang, Haitao (Frontiers in Public Health, 2024)
Objective: This meta-analysis aims to evaluate the global prevalence of mental disorders among young people living with HIV.Methods: A comprehensive search was conducted of the PubMed, Embase, and Cochrane Library databases for articles relevant to the study, published between January 2013 and June 2023. To identify sources of heterogeneity and compare prevalence estimates among various groups, subgroup analyses were conducted. Study heterogeneity was assessed using Cochran's Q and the I 2 tests. The robustness of the findings was ascertained through sensitivity analyses, while publication bias was evaluated with funnel plots and Egger's test.Results: 60 studies were included in this meta-analysis. It revealed that approximately one-quarter of YLWH experience depression, with a prevalence of 24.6% (95% CI: 21.1%-28.2%). The prevalence of anxiety was found to be 17.0% (95% CI: 11.4%-22.6%). Regarding suicidality, the prevalence of suicidal ideation and lifetime suicidal ideation in YLWH was 16.8% (95% CI: 11.3%-22.4%) and 29.7% (95% CI: 23.7%-35.7%), respectively. Additionally, the prevalence rates for suicidal attempts and lifetime suicidal attempts were 9.7% (95% CI: 4.0%-15.4%) and 12.9% (95% CI: 2.8%-23.1%), respectively. The prevalence of Post-Traumatic Stress Disorder and Attention Deficit Hyperactivity Disorder was identified as 10.5% (95% CI: 5.8%-15.2%) and 5.0% (95% CI: 3.1%-7.0%), respectively.The findings indicate a heightened risk of mental disorders among YLWH, underscoring the necessity for targeted intervention strategies to mitigate their suffering and potentially diminish the adverse impacts.